2003
DOI: 10.1523/jneurosci.23-20-07642.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Synaptic Contacts by Intranuclear Axon Collaterals of Thalamic Relay Neurons

Abstract: Relay neurons of the lateral geniculate nucleus innervate visual cortex, but they also provide axonal collaterals to neurons in the thalamic reticular nucleus, and these thalamic reticular neurons provide feedback inhibition to relay cells. An alternative source of inhibitory inputs onto geniculate relay neurons arises from intralaminar interneurons that provide feedforward inhibition via retinogeniculate innervation, and perhaps feedback inhibition via the corticothalamic pathway, analogous to that involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…RLD profiles were also observed by Montero (1989a), who found that these termi-nals could be labeled via tracer injections in the optic radiations dorsal to the PGN. Additionally, Montero (1989b) observed RLD profiles within the interlaminar zone (IZ) between the A and A1 laminae of the dLGN as well as within lamina A (Montero, 1991); this distribution correlates with an in vitro study, which found that dLGN interneurons are innervated by geniculocortical cells (Cox et al, 2003).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…RLD profiles were also observed by Montero (1989a), who found that these termi-nals could be labeled via tracer injections in the optic radiations dorsal to the PGN. Additionally, Montero (1989b) observed RLD profiles within the interlaminar zone (IZ) between the A and A1 laminae of the dLGN as well as within lamina A (Montero, 1991); this distribution correlates with an in vitro study, which found that dLGN interneurons are innervated by geniculocortical cells (Cox et al, 2003).…”
supporting
confidence: 67%
“…These anatomical results could explain the physiological results of Cox et al (2003). Using an in vitro preparation of the cat dLGN, these authors found that excitation of thalamocortical cells, via the pharmacological activation of metabotropic glutamate receptors, increased spontaneous miniature EPSPs recorded from interneurons in the A and A1 laminae.…”
Section: Rld Synaptic Contacts In the Dlgnmentioning
confidence: 77%
“…12, are likely valid in thalamic nuclei that do not contain interneurons, which are known as being a source of inhibitory inputs in TC neurons (e.g., see Ref. [46]). In the vibrissal system, closed-loop connections might be involved simultaneously in at least two subtle levels of integration: (1) a modular integration of information generated by the inputs activated by the principal whisker of the receptive field and (2) a more general integration of information generated by the inputs activated by adjacent whiskers.…”
Section: Closed-and Open-loop Thalamo-reticulo-thalamic Circuitsmentioning
confidence: 99%
“…Abundant fibers, presumably anterogradely labeled PC projecting axons, could be seen streaming laterally beyond the pulvinar, but these were not joined by any of the axons in our sample. Second, there are no reports from the monkey pulvinar nucleus that relay neurons have local collaterals, although we note that new reports have emerged noting that some relay neurons can have local collaterals, in the cat lateral geniculate nucleus (Cox et al, 2003) and rat paralaminar nuclei (Smith et al, 2006). Third, the radiate dendrites of PC projection neurons are reported to bear hairy appendages (Darian-Smith et al, 1999), but this was not the case for the long-range interneurons.…”
Section: Discussionmentioning
confidence: 78%